2020
DOI: 10.1192/bjo.2020.66
|View full text |Cite
|
Sign up to set email alerts
|

Stigma toward mental and physical illness: attitudes of healthcare professionals, healthcare students and the general public in Pakistan

Abstract: Background The evidence base for stigma in mental health largely originates from high-income countries. Aims This study from Pakistan aimed to address the gap in literature on stigma from low- and middle-income countries. Method This cross-sectional study surveyed 1470 adults from Karachi, Pakistan. Participants from three groups (healthcare professionals, healthcare students and the general public) completed the adapted Bogardus Social Distance Scale (SDS) as a measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…Unfortunately, mental health conditions are also more stigmatized than physical health conditions. A wealth of literature has found that mental health conditions (e.g., addiction, psychosis, depression, suicide) are seen as more “onset-controllable” (individuals are responsible or to blame for these conditions) and elicit less pity and willingness to assist than physical health conditions (e.g., cancer, diabetes, heart disease; Corrigan et al, 2000; Cryer et al, 2020; Husain et al, 2020; Weiner et al, 1988). Addiction seems to be especially stigmatized relative to other mental health conditions and physical disabilities (Corrigan et al, 2009; Rundle et al, 2021).…”
Section: Correlates Of Treatment-seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, mental health conditions are also more stigmatized than physical health conditions. A wealth of literature has found that mental health conditions (e.g., addiction, psychosis, depression, suicide) are seen as more “onset-controllable” (individuals are responsible or to blame for these conditions) and elicit less pity and willingness to assist than physical health conditions (e.g., cancer, diabetes, heart disease; Corrigan et al, 2000; Cryer et al, 2020; Husain et al, 2020; Weiner et al, 1988). Addiction seems to be especially stigmatized relative to other mental health conditions and physical disabilities (Corrigan et al, 2009; Rundle et al, 2021).…”
Section: Correlates Of Treatment-seekingmentioning
confidence: 99%
“…This study examined the prevalence of and willingness to seek treatment for physical and mental health problems in a racially diverse sample of Veterans. First, because mental health conditions tend to be more stigmatized than physical health conditions (Corrigan et al, 2009; Cryer et al, 2020; Husain et al, 2020), we hypothesized that Veterans would report greater willingness to seek treatment for physical than mental health conditions. Given the prevalence and elevated stigma associated with alcohol-related problems in military and Veteran populations (Barlas et al, 2013; Rundle et al, 2021), responses were examined both in the full sample and the subsample who reported hazardous drinking in the past year.…”
Section: Correlates Of Treatment-seekingmentioning
confidence: 99%
“…Contrary to other studies assessing this dimension, which have specifically focused on stigma towards individuals with substance use disorders (van Boekel et al, 2013), our results suggest that the higher perception of dangerousness and responsibility among GPs is unspecific and applies to mental illness in general. Score in these dimensions tends to depend on exposure to, and knowledge about, mental illness (Husain et al, 2020), both of which are higher among psychiatrists. As such, we argue that these results may reflect GP’s lack of knowledge and distorted social views on mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we found male physicians to exhibit significantly higher OS scores than female doctors, particularly in the dimensions of permanence, labelling, responsibility, diagnostic overshadowing and coercion . The influence of gender on stigma is controversial in the literature, as some studies report female doctors to express either more (Castillejos et al, 2018; Reavley et al, 2014), less (Eksteen et al, 2017; Husain et al, 2020) or similar (Cremonini et al, 2018) stigmatizing beliefs than their male colleagues. We propose these differences could be due to the individual’s cultural and educational background, and gender expectations in different countries/contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation